Time Course and Sex Effects of α-Linolenic Acid-Rich and DHA-Rich Supplements on Human Plasma Oxylipins: A Randomized Double-Blind Crossover Trial. Issue 3 (23rd October 2020) - Gabbs, Melissa; Zahradka, Peter; Taylor, Carla G; Aukema, Harold M
ABSTRACT: Background: Differences in health effects of dietary α-linolenic acid (ALA) and DHA are mediated at least in part by differences in their effects on oxylipins. Objectives: Time course and sex differences of plasma oxylipins in response to ALA- compared with DHA-rich supplements were examined. Methods: Healthy men and women, aged 19–34 y and BMI 18–28 kg/m 2, were provided with capsules containing ∼4 g/d of ALA or DHA in a randomized double-blind crossover study with >6-wk wash-in and wash-out phases. Plasma PUFA and oxylipin (primary outcome) concentrations at days 0, 1, 3, 7, 14, and 28 of supplementation were analyzed by GC and HPLC-MS/MS, respectively. Sex differences, supplementation and time effects, and days to plateau were analyzed. Results: ALA supplementation doubled ALA concentrations, but had no effects on ALA oxylipins after 28 d, whereas DHA supplementation tripled both DHA and its oxylipins. Increases in DHA oxylipins were detected as early as day 1, and a plateau was reached by days 5–7 for 11 of 12 individual DHA oxylipins and for total DHA oxylipins. Nine individual DHA oxylipins reached a plateau in females with DHA supplementation, compared with only 4 in males. A similar time course and sex difference pattern occurred with EPA and its oxylipins with DHA supplementation. DHA compared with ALA supplementation also resulted in higher concentrations of 4 individual arachidonic acids, 1 linoleic acid, and 1 dihomo-γ-linolenic acid oxylipin, despite not increasing the concentrations of these fatty acids, further demonstrating that oxylipins do not always reflect their precursor PUFA. Conclusions: DHA compared with a similar dose of ALA has greater effects on both n–3 and n–6 oxylipins in young, healthy adults, with differences in response to DHA supplementation occurring earlier and being greater in females. These findings can help explain differences in dietary effects of ALA and DHA. This study was registered at clinicaltrials.gov as NCT02317588.